NEW METHODOLOGICAL APPROACH TO ASSESSMENT OF SOCIOECONOMIC EFFICIENCY OF STATE PARTICIPATION IN DEVELOPMENT AND IMPLEMENTATION OF PROJECTS ON COMPREHENSIVE DEVELOPMENT OF TERRITORIES - Natalia V. Gorodnova; Alexander S. Stepanov (Advanced Engineering Research)
A methodological approach to the assessment of efficiency of the state participation in the projects on the comprehensive development of territories is offered. In this respect, a new form of the public-private partnership is implemented, whereas the present legal framework of the Russian Federation permits the governmental authorities at the regional level to grant building plots based on the innovative schemes.